On the Dual Basis of Projective Semimodules and Its Applications - Deore, R. P.; Patil, K. B. (Sarajevo Journal of Mathematics, 2024)
The dual basis lemma for projective semimodule over a semiring is proved. We show under which conditions the two categories $cs\, mod-R$ and $S-cs \,mod$ of cancellative semimodules are equivalent and how these equivalences are realized.